[LB.03.04] MODULATION OF MEMBRANE PROTEIN EXPRESSIONS IN ALDOSTERONE INDUCED HUMAN KIDNEY CELL VIA MICRORNAS. (September 2017) - Karakurt, S.
Abstract : Objective: Increased level of hypertension is found correlated with high aldosterone level in the adrenal gland. Aldosterone has a crucial role in blood pressure and its metabolism mainly controlled by modulation of relevant gene expressions by small, non-coding RNA molecules (miRNAs). The aim of this study is to investigate the mechanism of alteration of aldosterone metabolism related membrane proteins gene expressions. Design and method: In vivo hypertensive rat model was created by injection of aldosterone and expressions of 1680 miRNAs and 37000 rat transcriptome were investigated via miRNA and micro arrays, respectively. In situ analyses of arrays results alteration ratios of aldosterone metabolism, relevant genes and miRNAs were performed. In vitro human cell studies were performed by using human kidney cell line; NCI-H295r. The cells were pre-treated with aldosterone and alteration of gene and miRNA expressions was investigated by qRT-PCR. NCI-H295r cells transfected with human miRNA mimic and inhibitors in order to determine effects of miRNAs on membrane proteins' mRNA expressions. Results: Aldosterone injection to the rats increased systolic blood pressure 164 ± 2 mmHg from 118 ± 9 mmHg, which proved formation of hypertensive rats. In rat tissues, mRNA expressions of membrane proteins AGTR-1, and AGTR-2 were significantly increased 1.38-fold and 2.65-fold, respectively in the kidney (p < 0.001). In situ analyses of miRNA and mRNA expressions were showed that any of adrenal gland miRNAs are not related with aldosterone metabolism genes while kidney miRNAs were found relevant to aldosterone metabolism and 10 miRNAs were chosen. In vitro cell culture studies showed that has-miR-128-1-5p affects both mRNA expressions of AGTR-1 and AGTR-2. As a result of inhibition of expression of this miRNA (has-miR-128-1-5p) with miRNA mimic, AGTR-1 and AGTR-2 mRNA expressions were increased 14.2-fold and 2.3-fold, respectively. In a conclusion, hypertension was also regulated with alteration of miRNAs. Conclusions: Modulation of miRNAs might be one of the alternative cure for hypertension and has-miR-128-1-5p will be one of the candidates for the treatment of hypertension.